Exercise dependence, eating disorder symptoms and biomarkers of Relative Energy Deficiency in Sports (RED-S) among male endurance athletes - Torstveit, Monica Klungland (BMJ Open Sport Exerc Med, 2019)
OBJECTIVES: To explore associations betweenexercise dependence, eating disorder (ED) symptoms and biomarkers of Relative Energy Deficiency in Sports (RED-S) among male endurance athletes. METHODS: Fifty-three healthy well-trained male cyclists, triathletes and long-distance runners recruited from regional competitive sports clubs were included in this cross-sectional study. The protocol comprised the Exercise Dependence Scale (EXDS), the ED Examination Questionnaire (EDE-Q), measurements of body composition, resting metabolic rate, energy intake and expenditure and blood analysis of hormones and glucose. RESULTS: Participants with higher EXDS score displayed a more negative energy balance compared with subjects with lower EXDS score (p<0.01). EXDS total score was positively correlated with EDE-Q global score (r=0.41, p<0.05) and the subscale score for restraint eating (r=0.34, p<0.05) and weight concern (r=0.35, p<0.05). EXDS total score and the subscales lack of control and tolerance were positively correlated with cortisol (r=0.38, p<0.01, r=0.39, p<0.01 and r=0.29, p<0.05, respectively). The EXDS subscales withdrawal and tolerance were negatively correlated with fasting blood glucose (r=−0.31 and r=−0.32, p<0.05, respectively), while intention effect was negatively correlated with testosterone:cortisol ratio (r=−0.29, p<0.05) and positively correlated with cortisol:insulin ratio (r=0.33, p<0.05). CONCLUSION: In this sample of healthy male athletes, we found associations between higher EXDS scores, ED symptoms and biomarkers of RED-S, such as a more pronounced negative energy balance and higher cortisol levels.